Analisis Budaya Sekolah dalam Pembentukan Karakter di SMP IT Raudhatul Ulum Sakatiga Kecamatan Indralaya Kabuaten Ogan Ilir - Muhamad Altof; Mulyadi Eko Purnomo; Amir Rusdi (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This research was conducted with the aim to be able to analyze and describe more deeply about the academic and social culture at Raudhatul Ulum Sakatiga Middle School and find out how the characters formed at Raudhatul Ulum Sakatiga Middle School. This research methodology uses qualitative research methods with descriptive analysis methods and ethnographic research types. The primary data source of this study was obtained from observations, field notes (interviews). Secondary sources in this study were obtained from various sources consisting of books, dissertations, theses, theses, magazines, journals, articles, newspapers and data from the internet as well as writings that support the authenticity of credible and authoritative primary data. Furthermore, the data analysis technique in this study is to do data reduction, data presentation, and draw conclusions. Whereas in checking the validity data, the researcher uses four criteria, namely: trustworthiness, dependability, dependability, and certainty. Based on the analysis of the researchers' findings, it can be conveyed about the school culture at Raudhatul Ulum Sakatiga Junior High School which contains two aspects of culture, namely: 1) academic culture which includes reading culture, learning culture, creativity culture. 2) social culture that is attached to mutual support, 3S culture (smile, greetings, greetings), and simple living culture. The characters formed through school culture in Raudhatul Ulum Sakatiga Middle School ITS are: religious character, independent character, curiosity character, creative character, democracy character, discipline character, responsible character and social care character.